2022
DOI: 10.3390/v14020382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insertion and Deletion in the Meq Protein Encoded by Highly Oncogenic Marek’s Disease Virus on Transactivation Activity and Virulence

Abstract: Marek’s disease virus (MDV) causes malignant lymphoma in chickens (Marek’s disease, MD). Although MD is currently controlled by vaccination, MDV strains have continuously increased in virulence over the recent decades. Polymorphisms in Meq, an MDV-encoded oncoprotein that serves as a transcription factor, have been associated with the enhanced virulence of the virus. In addition, insertions and deletions in Meq have been observed in MDV strains of higher virulence, but their contribution to said virulence rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A large portion of these differences (n = 177 bp) corresponded to a 59 amino acid (AA) insertion in the meq oncogene, which was found in the CVI988 GenBank.BAC and CVI988 USDA.PA.field consensus genomes but absent in the CVI988 Pirbright.lab consensus genome (Figure 2). For meq, previous studies have suggested the existence of up to three isoforms: Meq, Long Meq (L-meq) and Short Meq (S-meq) (43)(44)(45)(46). Meq is the standard isoform and is 339-AA in length.…”
Section: The Meq Oncogene Contributes Significantly To Overall Intras...mentioning
confidence: 99%
See 1 more Smart Citation
“…A large portion of these differences (n = 177 bp) corresponded to a 59 amino acid (AA) insertion in the meq oncogene, which was found in the CVI988 GenBank.BAC and CVI988 USDA.PA.field consensus genomes but absent in the CVI988 Pirbright.lab consensus genome (Figure 2). For meq, previous studies have suggested the existence of up to three isoforms: Meq, Long Meq (L-meq) and Short Meq (S-meq) (43)(44)(45)(46). Meq is the standard isoform and is 339-AA in length.…”
Section: The Meq Oncogene Contributes Significantly To Overall Intras...mentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 4, 2023. ; https://doi.org/10.1101/2023.09.04.556264 doi: bioRxiv preprint the CVI988-UK consensus genome (Figure 2). For meq, previous studies have suggested the existence of up to three isoforms: Meq, Long Meq (L-meq) and Short Meq (S-meq) (39)(40)(41)(42).…”
Section: The Meq Oncogene Contributes Significantly To Overall Intras...mentioning
confidence: 99%
“…The transactivation domain includes proline-rich regions and determines the level of transcriptional regulation. Differences in the amino acid sequences of Meq (such as polymorphisms, insertions, and deletions) affect transcriptional regulation and the pathogenicity of MDV [ 15 , 16 , 17 ]. Four consecutive prolines (PPPP) present in the Meq region of classical MDV strains are characteristic of this proline-rich region [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a similar insertion was found in the proline-rich region of Meq of virulent MDV strains circulating in Australia, and PXPP substitutions were observed in the L-Meq proteins of these Australian strains [ 20 ]. Recent studies have shown that insertion into the proline-rich region increases the virulence of MDV [ 16 , 17 ], suggesting that the insertion contributes to the high virulence of MDV, whereas other factors, including polymorphisms in L-Meq, are involved in the low virulence of CVI988 [ 16 , 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation